2014
DOI: 10.1037/a0035714
|View full text |Cite
|
Sign up to set email alerts
|

The relation between television exposure and executive function among preschoolers.

Abstract: This study investigated the relations between television exposure during the preschool years and the development of executive function (EF). Data were gathered from 107 parents of preschoolers who provided information on children's television viewing, background television exposure, exposure to specific televised content, and the age at which children began watching television. Preschoolers' EF was assessed via one-on-one interviews. We found that several indicators of television exposure were significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
4
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(166 citation statements)
references
References 77 publications
7
148
4
5
Order By: Relevance
“…Of the 83 reported associations in 14 observational studies, between duration/frequency of childspecific TV content and cognitive development, nine (11%) were statically significant detrimental associations 33,41,42,50,52,56,58 and nine (11%) were statistically significant beneficial associations. 41,42,46,52,57 Three studies reported beneficial associations with cognitive development for some content (educational, ABC and PBS channel viewing), and detrimental associations for Figure 3 displays the number of statistically significant detrimental, statistically significant beneficial, and null associations between higher or increased child-specific TV content and cognitive development outcomes stratified by cognitive domain.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Of the 83 reported associations in 14 observational studies, between duration/frequency of childspecific TV content and cognitive development, nine (11%) were statically significant detrimental associations 33,41,42,50,52,56,58 and nine (11%) were statistically significant beneficial associations. 41,42,46,52,57 Three studies reported beneficial associations with cognitive development for some content (educational, ABC and PBS channel viewing), and detrimental associations for Figure 3 displays the number of statistically significant detrimental, statistically significant beneficial, and null associations between higher or increased child-specific TV content and cognitive development outcomes stratified by cognitive domain.…”
Section: Resultsmentioning
confidence: 88%
“…41,42,46,52,57 Three studies reported beneficial associations with cognitive development for some content (educational, ABC and PBS channel viewing), and detrimental associations for Figure 3 displays the number of statistically significant detrimental, statistically significant beneficial, and null associations between higher or increased child-specific TV content and cognitive development outcomes stratified by cognitive domain. Three experimental studies had an exposure of non-screen based sedentary behavior.…”
Section: Resultsmentioning
confidence: 95%
“…Recent studies show, however, that the earlier the mobile device is introduced in early childhood, the worse the child's attentional and cognitive outcomes may be. 16 Instead, clinicians can remind parents that they are their child's best teacher, and the best application cannot parallel the developmental benefits of hands-on, unstructured, face-to-face, or outdoors play. 17 When children do learn new things from applications or educational programming, parents should help their child apply this new knowledge to the 3-dimensional world around them 14,18 by exploring the new concept through play or conversation, rather than allowing the prolonged play that can result from games or videos automatically advancing.…”
Section: Discussionmentioning
confidence: 99%
“…59 -62 Possible mechanisms for these outcomes include the effects of viewing inappropriate, adult-oriented content 54 (as well as some inappropriate child-directed content), 58 a decrease in parent-child interaction when the TV is on, 63 and poorer family functioning in households with high media use. 60 An earlier age of media use onset, greater cumulative hours of media use, and content that is not of high quality all are significant independent predictors of poor executive functioning (impulse control, self-regulation, mental flexibility) 33 as well as "theory of mind" deficits (ie, the ability to understand others' thoughts and feelings) in preschoolers. 64 Media multitasking, once thought to be a pastime only of only adolescents, now is observed even in children younger than 4 years.…”
Section: Health and Developmental Risks Of Media Use What Are The Devmentioning
confidence: 99%
“…33 Preschoolers randomly assigned to change from inappropriate or violent content to high-quality prosocial programming were found to have significant improvements in their externalizing and internalizing behavior, 32 which also speaks to the importance of content. For families who find it difficult to modify the overall amount of media use in their homes, changing to high-quality content may be a more actionable alternative; to make these changes, pediatric providers can direct them toward curation services, such as Common Sense Media, for reviews of videos, apps, TV shows, and movies.…”
Section: What Is the Best Approach To Selecting Quality Content For Ymentioning
confidence: 99%